Preliminary Study on Various Shaped Models of Delivery valve in Hydraulic Ram Pump – Experimental Results - Made Suarda; I Gusti Bagus wijaya Kusuma; Made Sucipta; Ainul Ghurri (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2020)
Four shaped models of delivery valve had been investigated and compared to improve performance of a hydraulic ram. Hydraulic ram pumps have been constructed and operated. Most of them built locally using steel pipe fittings that commercially accessible in the market rather than factory-made one. These have assisted inhabitants in rural or hilly area where water sources available for water supply services or irrigations. However, the major problem challenged by the public was on designing and repairing of the impulse and delivery valves of the pumps. Performance of the pumps are affected predominantly by the both valves. One characteristic of the valves is their shape. Considered on the characteristics of the fluid flow through surface of plate and sphere object are different on the pattern and losses. Therefore, investigation is necessitated to find a proper shape of the delivery valve for enhancing the performance of the pump. In this research four valve models were experimented to assess the hydraulic ram pump performance on varies delivery heads. The results show that the sphere model of the delivery valve offered the best efficiency, then followed by the membrane, the half-sphere and the flat delivery valve models. However, the rounded model: sphere and half-sphere delivery valve model were facing obstructions in implementation for a high delivery head.